Socio-Psychological Competence of the Teacher: Readiness for Dialogue through the Organization of Communication (Discussion within the Framework of the Conference in Memory of M.Yu. Kondratiev "Social Psychology: Questions of Theory and Practice") - Bazarov, T.Y.; Dubovskaya, E.M.; Zueva, E.A. (Socialʹnaâ Psihologiâ i Obŝestvo, 2023)
The article presents a report on the round table "Socio-psychological competence of teachers: readiness for dialogue through the organization of communication", held in the framework of the VIII International Scientific and Practical Conference in memory of M.Yu. Kondratiev "Social Psychology: Issues of Theory and Practice", which took place on May 11-12, 2023 at the Moscow State University of Psychology & Education. The article lays out main directions of discussions within the framework of the round table, the problems identified during the discussions and their relevance for the research and practical activities of social and educational psychologists. В статье представлен отчет о работе круглого стола «Социально-психологическая компетентность учителя», проведенного в рамках VIII Международной научно-практической конференции памяти М.Ю. Кондратьева «Социальная психология: вопросы теории и практики», которая состоялась 11-12 мая 2023 года в Московском государственном психолого-педагогическом университете. Отражены основные направления дискуссий в рамках круглого стола, обозначенные в ходе дискуссий проблемы и их актуальность для исследовательской и практической деятельности социального психолога и психолога образования.